Antimicrobial activity of Goat Milk Casein generated by Lactic Acid Bacteria used against Cronobacter Sakazakii - Ibrahim Mustafa Elshaafi (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc)-- Faculty of Science and Technology, Universiti Sains Islam Malaysia, 2015